Supramolecular polypseudorotaxane with conjugated polyazomethine prepared directly from two inclusion complexes of β-cyclodextrin with tolidine and phthaldehyde - Zhang, Xin Zheng (2011)
The supramolecular polypseudorotaxane (3) with π-conjugated polyazomethine is directly